Co-transplantation of Epidermal Neural Crest Stem Cells and Olfactory Ensheathing Cells Repairs Sciatic Nerve Defects in Rats - Zhang, Lu; Li, Bingcang; Liu, Bin; Dong, Zhifang (Frontiers in Cellular Neuroscience, 2019)
Cell-based therapy is an alternative strategy to improve outcomes of peripheral nerve injury (PNI). Epidermal neural crest stem cell (EPI-NCSC) is obtained from autologous tissue without immunological rejection, which could expand quickly in vitro and is suitable candidate for cell-based therapy. Olfactory ensheathing cell (OEC) could secrete multiple neurotrophic factors, which is often used to repair PNI individually. However, whether the combination of EPI-NCSC and OEC have better effects on PNI repair remains unclear. Here we use EPI-NCSC and OEC co-transplantation in a rat sciatic nerve defect model to ascertain the effects and potential mechanisms of cells co-transplantation on PNI. The effect of EPI-NCSC and OEC co-transplantation on PNI is assessed by using a combination of immunohistochemistry (IHC), electrophysiological recording and neural function test. Co-transplantation of EPI-NCSC and OEC exerts a beneficial effect upon PNI such as better organized structure, nerve function recovery, and lower motoneuron apoptosis. IHC and ELISA further demonstrate that cells co-transplantation may improve PNI via the expression of BDNF and NGF up-regulated by EPI-NCSC and OEC synergistically. Eventually, the results from this study reveal that EPI-NCSC and OEC co-transplantation effectively repairs PNI through enhancing the level of BDNF and NGF, indicating that cells co-transplantation may serve as a fruitful avenue for PNI in clinic treatment.